ULTRASONIC TREATMENT EFFECT ON THE CONSOLIDATION OF Fe-Cr PARTICLE MIXTURES AFTER COMPACTION AND SINTERING PROCESS - Silalahi, Marzuki; Untoro, Pudji; Suharno, Bambang; Harjanto, Sri (Pusat Penelitian Metalurgi dan Material - LIPI, 2014)
ULTRASONIC TREATMENT EFFECT ON THE CONSOLIDATION OF Fe-Cr PARTICLEMIXTURES AFTER COMPACTION AND SINTERING PROCESS. Fe-Cr microalloys which obtained byultrasonic method are the initial cores for the consolidation process. Therefore its facilitate the formation of thehomogeneous bulk of Fe-Cr alloy with a stable phase. In this research, the synthesis of bulk of Fe-Cr alloy fromthe particles mixture of (Fe+Cr) as the ultrasonic treatment results has been carried out. The particlesconsolidation has been carried out through a process of compaction without adding any lubricants and followedby sintering process in the quartz glass capsules by using induction furnace at 1300 °C. Consolidation of mixtureof Fe-Cr particles that have not undergone previous ultrasonic treatment is also made for a comparison. Theinvestigation by using the SEM (scanning electron microscope)- and density measurements method werepreformed on the Fe-Cr green powders compaction. The bulk of Fe-Cr alloys that are produced trough sinteringprocess was observed using SEM-EDS (energy dispersive spectroscopy), XRD (x-ray diffraction), and densitymeasurements method. The bulk of Fe-Cr alloy prepared with ultrasonically treated Fe-Cr microalloy powders,is more homogeneous in composition and has a better phase stability in comparison to Fe-Cr powders preparedwithout the ultrasonic treatment. Production of bulk Fe-Cr alloy in quartz glass capsule during the sinteringprocess has produced Fe-Cr alloy without oxides.